"Best Practices" and Collaborative Software In Online Teaching - Remi Tremblay (Athabasca University Press, 2006)
In recent years, many distance educators and institutions have successfully adopted asynchronous text-based environments as the backbone of their online classrooms. Group email, electronic references, and course websites, coupled with online discussions, typically constitute the model of online course delivery. Although the structure and pacing of these asynchronous text-based environments provide both students and instructors with increased flexibility and convenience, the synchronicity and sometimes the freshness of the interaction of the traditional face-to-face classroom were often sacrificed.